2020
DOI: 10.1007/s00296-020-04593-6
|View full text |Cite|
|
Sign up to set email alerts
|

Osteoporosis in patients with rheumatoid arthritis: trends in the German National Database 2007–2017

Abstract: Osteoporosis is a frequent comorbidity in rheumatoid arthritis (RA). Due to the improved treatment options for RA, we expect a long-term decrease in osteoporosis as an accompanying disease. Data from the German National Database (NDB) were used to investigate whether the frequency of osteoporosis has changed in the last 10 years. From 2007 to 2017, approximately 4000 patients were documented annually with data on therapy and comorbidity. The cross-sectional data were summarised descriptively. Age, sex, disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
1
16
0
2
Order By: Relevance
“…Furthermore, previous studies have described that the risk of fracture in the next 10 years measured by FRAX is increased in ACPA positive patients (17). By contrast, recent publications show that patients achieving early RA remission have a similar OP risk profile than the general population (15).…”
Section: Osteoporosis Risk Factors In Ramentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, previous studies have described that the risk of fracture in the next 10 years measured by FRAX is increased in ACPA positive patients (17). By contrast, recent publications show that patients achieving early RA remission have a similar OP risk profile than the general population (15).…”
Section: Osteoporosis Risk Factors In Ramentioning
confidence: 97%
“…Other biological agents such as tocilizumab, rituximab, and abatacept have shown a significant decrease in bone resorption markers and RANKL expression, which provides evidence of a beneficial effect on bone remodeling process slowing down bone loss (15). In a study, a 2-year treatment with tocilizumab showed improvement in BMD and significantly decreased levels of β-CTX in ACPA positive patients (97).…”
Section: Something Is Changing In Osteoporosis Associated With Ramentioning
confidence: 98%
See 3 more Smart Citations